A Novel EMD Mutation Identified by Whole-Exome Sequencing in Twins with Emery–Dreifuss Muscular Dystrophy. (24th August 2020) - Dai, Xiafei; Luo, Rong; Chen, Yang; Zheng, Chenqing; Tang, Yibin; Zhang, Hongmei; Su, Ye; He, Tao; Li, Xiaoping
Abstract : This case reports a novel hemizygous frameshift EMD mutation (c.487delA, p.Ser163fs) in twins of an Emery–Dreifuss muscular dystrophy family with severe cardiac involvement and mild muscle weakness. Their mother carried the same heterozygous mutation.